Gambaran Math anxiety pada Siswa SMA - Mikaela Berliyana Alitani; Yeny Duriana Wijaya (Departement of Mathematics Education, 2024)
Math is very necessary in everyday life. However, mathematics literacy in Indonesia is still low. Some students who have low mathematical literacy skills are associated with Math anxiety. Math anxiety is a student's emotional state that causes students avoid math lessons. The student felt symptoms of physical pain, dizziness, fear and panic when they are studying math. Students also find difficulties when they do math, they avoid math classes. And can’t do math test questions. As a result, their mathecatical performance is decreases. This research provide an overview of Math anxiety in high school students. This type of research is descriptive research with a random sampling technique involving 100 high school students aged 15 to 21 years. The results of this research show that 56% of high school students experience Math anxiety in the high category and 44% in the low category.